AB0144 Nmr based serum and synovial fluid metabolomics reveal similar metabolomic profile in patients with reactive arthritis and undifferentiated spondyloarthropathy. (12th June 2018) - Misra, R.; Dubey, D.; Ahmed, S.; Chaurasia, S.; Chaudhary, S.; Guleria, A.; Kumar, D.
Abstract : Background: Reactive arthritis (ReA)and undifferentiated spondyloarthropathy (USpA) have similar clinical picture, the former is prededed by mucosal infections and the latter do not meet criteria of well defined entity of seronegative spondyloarthropathy (SSA) We have shown that both ReA and uSpA have similar synovial fludid T cell response to salmonella antigens and cytokine profile. Objectives: To investigate if the metabolic profiles of ReA in sera and synovial fluid are different from those of USpA Methods: Standard defnitions were used to classify patients as ReA 2 and uSpA 3 Metabolic profiles in sera and synovial fluid samples were measured using 1D 1 H NMR spectroscopy and analysed using CHENOMX© software. The quantitative profiles between the groups were compared using Partial Least Square-Discriminatory Analysis (PLS-DA) and Q 2 parameter was used to assess the metabolic differences between the groups. Results: The study involved 19 ReA and 13 USpA patients with median age 26 (21–33.75) years. Of 32 patients: 7 (22%) were females, three(12%) had monophasic illness, 16 (64%) polyphasic, and six(24%) persistent arthritis (follow-up data was not available for 7). 27% had monoarticular, 59% oligoarticular and 14% polyarticular involvement. Six had inflammatory backpain, three had oral ulcers, one dactylitis, but none had mucocutaneous manifestations. Two had asymptomatic sacroiliitis on radiographs. Compared to normal controls (n=18, median age=29 years, male:female=17:1), the sera of ReA/USpA patients were characterised by elevated levels of malonate, mannose, N-nitrosodimethylamine, and pyruvate, whereas 3-hydroxyisovalerate was decreased significantly (T-test p-value<0.001). PLS-DA analysis between sera and synovial fluid samples showed clear demarcation with higher pyruvate and acetoacetate and lower aspartate, methanol, ethanol, and methylsuccinate in synovial fluid samples compared to sera (t-test p<0.01). The PLS-DA analysis of sera showed little difference between ReA and USpA (figure 1) while that of synovial fluid showed Q 2 <0 for all models. Further no significant metabolic differences in sera/synovial fluid were found between HLA-B27 positive and negative groups (Q 2 <0 in all models). Conclusions: ReA and USpA have indistinguishable metabolomics profiles in sera and synovial fluid reflecting similar metabolo-inflammatory pathways involved. References: [1] Chaurasia S, Shasany AK, Aggarwal A, Misra R. 2016Aug;185(2):210–8. [2] Braun J, Kingsley G, et sl. Journal of Rheumatology2000;27:2185–92. [3] Sieper J, Rudwaleit M, et al. Ann Rheum Dis. 2009Jun;68(Suppl 2):ii1–44. Disclosure of Interest: None declared